HGG-32. ARG-AUXOTROPHIC PATIENT-DERIVED GLIOBLASTOMA MULTIFORME CELL LINES SHOW INCREASED SENSITIVITY TOWARDS DOXYCYCLINE-INDUCED GROWTH INHIBITION. Issue 2 (22nd June 2018) - Shokraie, Fatemeh; Riess, Christin; Fiedler, Tomas; Schneider, Björn; Classen, Carl Friedrich; Maletzki, Claudia
Abstract: Arginine auxotrophy constitutes a metabolic defect that renders tumors susceptible towards arginine-depleting substances, such as bacterial arginine deiminase (ADI). In our previous studies, Arg auxotrophy and thus ADI-susceptibility was confirmed on patient-derived GBM models in vitro and in vivo. Functionally, effects were attributable to induction of autophagy, senescence and necrosis. To improve this approach, we here examined whether ADI-treatment may be combined with doxycycline (Dox) - an antibiotic with anti-cancer activities by targeting mitochondria. The effect of doxycycline was first investigated on a panel of patient-derived GBM cell lines to determine general sensitivity (N=8). Analysis revealed higher susceptibility of Arg-auxotrophic compared to Arg-prototrophic cells (N=4 cell lines each). Thereafter, doxycycline (IC20 ) was combined with ADI (35 mU/mL) in simultaneous and sequential regimens (72h each). Combined application of both agents slightly enhanced antitumoral effects of the monotherapy in selected cell lines. Decreased mitochondria content after Dox treatment was confirmed by immunofluorescence and quantitative PCR. This effect was only partially counteracted after the combination. Instead, necrosis was the dominating mode of cell death, while autophagy was found to play a minor role. No effect on radiosensitivity was seen in either treatment regimen, i.e. simultaneous or sequential. Taken together, our data support the conclusion that ADI can be combined with substances impairing mitochondria function, likely to result in an efficient oncolytic regimen. Ongoing trials focus on improvement of the treatment protocol by implementing this approach into standard clinical drug regimen and in vivo testing.